Exploring Islamic Work Ethics through Dimensional Analysis in Socially Nuanced Economic Institutions - Wijiharta; Wening, Nur (International Journal of Indonesian Business Review, 2022)
Purpose –This study aims to determine the level of assessment of Islamic work ethics by responses from sosially nuanced economic institutions employees Methodology/approach – The survey was conducted on 10 socially nuanced economic institutions in Indonesia. 30 respondents of KSPSS employee were willing to fill out a survey questionnaire on Islamic Work Ethics. Findings – It was found that the spirituality dimension of Islamic Work Ethics has a higher average than other dimensions, with an average score of 4,483. The next order is the social dimension, the economic dimension, the psychological dimension and the philosophical dimension. Novelty/value – in a materialistic hedonistic lifestyle, the work ethics of employees of sosially nuanced economic institution, KSSPS, has a higher spiritual dimension than the economic and social dimensions